The importance of adopting blockchain technology in enhancing cybersecurity in the banking sector - boukhezar, omaima; djekrif, ALI (Journal of Research in Finance and Accounting, 2024)
This study aimed to identify the extent to which blockchain technology contributes to enhancing cybersecurity. Through this research paper, we try to identify blockchain technology, its characteristics, types and elements, and to identify cybersecurity and cyberthreats. We shed light on the analysis of the size of the blockchain and cybersecurity market for global banking services by following the descriptive analytical approach. Through this study, we conclude that the synergy between blockchain technology and cybersecurity is expected to transform the future of banking services. By integrating blockchain technology with advanced cybersecurity measures, banks can create a secure and efficient banking system.